A Novel Approach to Solving Singularly Perturbed differential algebraic equations: Regularized Laplace Homotopy Perturbation Method - Farhan, Khalid (Statistics, Optimization & Information Computing, 2025)
In this paper, we used the Laplace Homotopy Perturbation Method (LHPM) to solve the system of Singularly Perturbed differential algebraic equations (DAEs) with an initial condition. We have added an optimization parameter to LHPM to obtain more accurate solutions . Examples are solved using the method presented in this paper, and the calculated results were compared with the Rung-Kutta and Euler methods to observe the accuracy and efficiency of the proposed method.